To smoke or not to smoke: Does delay discounting affect the proximal choice to smoke?. (3rd July 2019) - Sheffer, Christine E.; Prashad, Neelam; Lunden, Sara; Malhotra, Ria; O'Connor, Richard J.
Abstract: Background: Delay discounting rate shows robust predictive validity for tobacco use behaviors and is a new therapeutic target in the treatment of tobacco use. Identifying factors that influence relations between delay discounting and the choice to smoke cigarettes is key to the development of effective interventions that target delay discounting to reduce cigarette consumption. Objective: To examine relations between delay discounting, motivational factors, self-efficacy, nicotine dependence level, and the proximal choice to smoke in the context of other commonly rewarding activity choices. Methods: In this cross-sectional design, daily smokers ( n  = 480) from Amazon Mechanical Turk completed a questionnaire that assessed delay discounting rate; motivation, intention, and self-efficacy to quit smoking; nicotine dependence level, and the preference for immediately engaging in multiple commonly rewarding activities. We hypothesized that 1) greater motivation to quit would be associated with lower priority given to smoking; 2) the relation between delay discounting and the priority given to smoking would be mediated by motivation, self-efficacy, and nicotine dependence level. Results: Greater motivation to quit was significantly associated with a lower priority given to smoking. The relation between delay discounting and the priority given to smoking was marginally mediated by nicotine dependence level ( p > .057). Conclusions: Motivation to quit influences decision-making by impacting the prioritization of choices. Nicotine dependence is likely to mediate the relation between delay discounting and the choice to smoke. Interventions that target delay discounting to reduce cigarette consumption or prevent relapse need to account for motivation to quit and nicotine dependence level.